High School Students’ Difficulties in Writing Descriptive Text - Wardah Hafizah; Nida Husna; Neneng Sunengsih; Maulidya, Reza Anis (Universitas Pendidikan Ganesha, 2024)
Difficulty in writing descriptive text is still a problem experienced by high school students. The aim of this research is to find out the mistakes and difficulties that students most often experience in writing descriptive texts. The method used in this research is a qualitative descriptive method. The sample for this research consisted of 36 tenth grade students from a state high school and was selected using a purposive sampling technique. The instruments used in this research were writing tests and interviews with data analysis techniques using descriptive statistics. The research results showed that 0.1% of students made mistakes in the content aspect, 0.1% in the organizational aspect, 8.3% in vocabulary, 23.5% in language use, and 68% in mechanics. The results of the analysis show that the largest number of errors is in the mechanical aspect with a total of 1085 errors. The difficulties experienced by students in writing descriptive texts lie in the aspects of vocabulary, language use, and mechanics. This is due to lack of vocabulary, grammar skills, and writing in a hurry. To overcome this problem, students can learn and practice English through online platforms such as Google Translate and YouTube. Students must also increase their focus on writing practice and always proofread their writing. Through this research, it is necessary to develop a learning program that focuses on increasing vocabulary, grammar skills, and applying appropriate mechanics in writing descriptive texts for high school students.